COEXISTING FOETUS AND HYDATIDIFORM MOLE - Mufti, Shaheen; Begum, Nazakat (Journal of Ayub Medical College Abbottabad, 1991)
ABSTRACT: Coexisting foetus with mole is very rare. A case of partial Hydatidiform mole in a grandmulitiparous patient is presented. Hysterectomy and bilateral abdominal sterilization by Pomeroy method was performed.